Oral Contraception Use in Benign Breast Tumor Patients in Dr. Soetomo General Academic Hospital - Ayu Maghfira Nida Putri; Sjahjenny Mustokoweni; Ernawati Ernawati (Health Notions, 2019)
The growth of breast tumors is influenced by estrogen and progesterone hormones. One source of this hormone is hormonal contraception, including oral contraception which still in demand by Indonesian women. This study wants to identify oral contraception use in patients with benign breast tumors. This used descriptive study with a retrospective cross-sectional design. Samples were taken using the total sampling method in patients with benign breast tumors according to ICD 10 D-24 which was confirmed by FNAB examination at the POSA Dr. Soetomo General Academic Hospital between 2015-2017. Fifty three case of benign breast tumor were found with dominant characteristics at the age of group 40-49 years old (47.2%), had a breastfeeding history (50.9%), multiparous woman(64.2%), mean of menarche age at 13.28 years old and fertile periode women (83.0%). The most common type of benign tumors found were fibrocystic change. Patients who used oral contraceptives were 24.5% with an average length of use for 8 years 2 months, while another 75.5% used non-hormonal contraception or did not use any contraception. So the conclusion is majority of patients with benign breast tumors do not use oral contraception. Keywords: benign breast tumor; oral contraception; estrogen